Improvement of P Use Efficiency and P Balance of Rice–Wheat Rotation System According to the Long-Term Field Experiments in the Taihu Lake Basin - Xiao, Liang; Chen, Guanglei; Wang, Hong; Li, Yixuan; Li, Chi; Cheng, Liang; Wu, Wenge; Xiao, Xin; Zhu, Yiyong (Frontiers in Environmental Science, 2022)
Phosphorus (P) accumulation in rice–wheat rotation fields around the Yangtze River delta have been enriched during the last decades. To protect the environment and save P resources, we conducted field experiments to optimize the P application scheme. First, one field experiment was designed as a series of P fertilizer application doses of 0–100 kg P2O5 hm−2. Grain yield and P uptake by crops were analyzed to calculate P surplus and P use efficiency. Soil P fractions were extracted and tested. According to the P balance, we optimized fertilization by reducing the chemical P amount, which was used by local farmers; furthermore, we substituted chemical P with organic fertilizer. To verify these management strategies, another field experiment was conducted with five treatments: no N, P, or K fertilizer (CK); only no P fertilizer (NK); farmers’ fertilization of P (90 kg P2O5 hm−2) (FFP); reducing 20% P (FFP-20%P); and reducing 20% P and replacing 20% P by manure (FFPM-36%P). The grain yield was enhanced by increased P fertilizer and reached a constant level after 75 kg P2O5 hm−2. Moreover, the annual P surplus was balanced around the input of 150 kg P2O5 hm−2. Accordingly, by optimizing fertilization (FFP-20%P) and further replacing manure (FFPM-36%P), we also achieved crop yield equivalent to that of FFP treatment (90 kg P2O5 hm−2). Thus, the 72–75 kg P2O5 hm−2 application rate is a threshold for the production of rice and wheat and P balance. Total P content in soil was enhanced by increased input of P fertilizer and mainly divided into labile Pi and middle stable Pi fractions. Soil Olsen-P content increased by P fertilization accordingly, while the content of organic P and stable P content was relatively constant. Reducing P fertilizer by 20% had similar results for soil P fractions when compared with farmers’ P fertilization treatment. Therefore, reducing at least 20% current input of P by farmers (annual 180 kg P2O5 hm−2) according to the balance of P surplus in rice and wheat rotation systems is an imperative measure to guarantee crop production with enhanced P use efficiency, and meanwhile, it can alleviate environmental risk.